Pollution and the efficiency of urban growth - Martin F. Quaas; Sjak Smulders (Fondazione Eni Enrico Mattei (FEEM), 2008)
We analyze the efficiency of urbanization patterns in a dynamic model of endogenous urban growth with two sectors of production. Production exhibits increasing returns to scale on aggregate. Urban environmental pollution, as a force that discourages agglomeration, is caused by domestic production. We show that cities are too large and too few in number in equilibrium, compared to the efficient urbanization path, if economic growth implies increasing aggregate emissions. If, on the other hand, production becomes cleaner over time (`quality growth') the urbanization path approximates the efficient outcome after finite time.
Keywords: Q56; R12; O18; 330; Cities; Urbanisation; Pollution; Growth; Migration; Sustainable Development